SOSIALISASI ASPEK PERPAJAKAN BAGI YAYASAN YANG BERGERAK PADA BIDANG PENDIDIKAN - Dewi, Siti Ratna Sari; Khotimah, Husnul; Umam, Danang Choirul (Jurnal Abdi Masyarakat Multidisiplin, 2024)
This community service activity aims to enhance the understanding of foundation administrators regarding tax obligations, including types of taxes, reporting, and payment using technology such as e-filing. Through lectures, discussions, and hands-on simulations, participants gained theoretical knowledge and practical skills in managing tax obligations. Evaluation results showed a significant increase in participants' understanding, which positively impacted the efficiency and accountability of the foundation's governance. This program serves as a strategic model to support the professionalism of other educational foundations